Holmium Laser Endourethrotomy for the Treatment of Long-Segment Urethral Strictures: A Retrospective Study of 190 Patients - Liu, Qigui; Ma, Weiqing; Li, Xin; Zhang, Wentao; Cao, Wei; Zhou, Qingyu; Duan, Juan (Urology Journal, 2014)
Purpose: Long-segment urethral strictures (LSUS) are refractory to urethrotomy and urethroplasty. Holmium laser urethrotomy has shown favorable therapeutic outcomes in short-segment urethral stricture. We therefore evaluated the therapeutic effectiveness and safety of holmium laser endourethrotomy in the treatment of LSUS. Materials and Methods: Holmium laser endourethrotomy was used to treat 190 consecutive male patients with LSUS. A urethrocystoscopic poking maneuver incorporating holmium laser ablation was used to eliminate the urethral strictures completely. Maximum flow rate (Qmax) on retrograde uroflowmetry, International Prostate Symptom Score (IPSS) and the Expanded Prostate Cancer Index Composite (EPIC) quality of life (QoL) index were assessed at baseline and at 1-, 3- and 6-months postoperatively. Results: Holmium laser urethrotomy was successfully completed in all 190 patients. The mean operation time was 25 ± 17.8 min (range, 6-69 min). No significant intraoperative complications occurred, except that 23 patients (12.1%) experienced controllable scrotal and penile edema. None of these LSUS patients experienced recurrent strictures during a follow-up period of 6-36 months. From baseline to 6 months postoperatively, the mean Qmax increased significantly, from 1.4 ± 2.7 mL/sec to 19.7 ± 4.1 mL/sec (P < .001); mean IPSS decreased significantly, from 31.3 ± 7.2 points to 9.3 ± 3.1 points (P < .001); and mean QoL score showed significant improvement, from 5.7 ± 1.6 points to 1.8 ± 0.4 points (P < .001). Conclusion: Holmium laser endourethrotomy with the poking maneuver is a therapeutically effective and minimally invasive treatment for LSUS.